LOCAL WISDOM IN THE ORAL TRADITION OF THE PEOPLE’S BELIEF ON PROHIBITION EXPRESSION IN CATEGORIES HUMAN LIFE OF MINANGKABAU SOCIETY IN LUHAK NAN TIGO AREA - Hasanuddin WS; Novia Juita (International Conference on Languages and Arts, 2014)
This paper is talking about the oral tradition of the people belief of prohibition expression in categories about human life of Minangkabau society in custom areas Luhak Nan Tigo on the framework of the study of oral literature, oral traditions, and folklore. The people belief of prohibition expression in categories about human life is divided into the following subcategories, namely subcategories pregnancy, infancy, and childhood, the human body subcategories and folk medicine; subcategories home and housework; subcategories livelihoods and social relations; subcategories travel and transportation; subcategory of the romance, engagement, and marriage; and subcategories death and funeral customs. Talks about the people belief are related to the conviction, while the conviction is closely linked with the traditions and customs. All of them are summarized in two main points that are culture and ideology. Thus, when dealing with belief, including the people belief of prohibition expression in the oral literary should be placed on the framework that the problem is not whether it can be proven or not, true or not, but rather on how the values ​​contained in the text of prohibition expression functioning in the social community. Local wisdom which is form of the values ​​and philosophy of life is able to develop integrity of the society, a tool of social control, combining strength that are broke for social solidarity, group identity, and communal harmony. The functions give a signal that every society needs conviction, other conviction that can support life creativity in togetherness. Keywords: local wisdom, folk beliefs, prohibition expressions, Minangkabau society, Luhak Nan Tigo, folklore.